Cargo Loading and Unloading Efficiency Analysis in Multimodal Transport - Burdzik, Rafał; Cieśla, Maria; Sładkowski, Aleksander (Promet - Traffic&Transportation, 2014)
The paper presents assessment of the impact of the processes handling efficiency on the transport process based on research done in the real object, using same technologies and material handling equipment. The aim of the paper was to confirm importance of loading and unloading processes of palletized cargo as an initial and final link of multimodal transport by developing methods’ proposal for monitoring and assessing the effectiveness of cargo operations as well as development of measures and comparison estimators. The analysis of the manipulation operations’ duration throughout the transport process is based on the percentile rates of manipulation and carriage in total transport process duration and the percentage of manipulating time in the duration of the carriage. These indicators and examined loading and unloading times, are the basis for the development of scheduling algorithms for optimizing transport processes on the scale of the whole transport chain. This data is also a helpful input to support strategic decisions on the allocation of financial resources for the development of infrastructure and terminal equipment, warehouses and other facilities.